Accessibility and reachability of disabled people in shopping complex at Kuala Lumpur (case study: Pertama Complex, Ampang Park and Sungei Wang Plaza) / Faradilla Aini Ahmad Azman - Ahmad Azman, Faradilla Aini (2004)
The lacking of disabled facilities has been discussed for a long time. Many parties involved for the issue of facilities for disabled people. Mass media is an important party to raise the issue of lacking of disabled people to publics. The government has been planned to improve the issue including established the specific Act and policy. However many buildings are still not provide appropriate disabled facilities. Nowadays, many existing buildings which have been upgrade try to improve the facilities as to compete to new buildings. However the building’s managers are still not consider about disabled facilities. The facility for disabled people has been abandoned by building’s manager. Some of facilities provided not following the appropriate standard requirement. Therefore the author hopes with this study, it will helped the relevant parties to take an action on existing buildings by refer to case study at Pertama Complex, Ampang Park and Sungei Wang Plaza.